1999
DOI: 10.1023/a:1006981411691
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Activation of Raf-1 kinase is preceded by a translocation of Raf-1 to the plasma membrane in response to external stimuli. The membrane localization of Raf-1 is facilitated through its interaction with activated Ras and with membrane phospholipids. Previous evidence suggests that the interaction of Raf-1 with Ras is mediated by two distinct domains within the N-terminal region of Raf-1 comprising amino acid residues 51-131 and residues 139-184, the latter of which codes for a zinc containing cysteine-rich doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 41 publications
5
30
0
Order By: Relevance
“…5). Taken together, our results with respect to lipid binding performed with purified and functional full-length C-Raf kinases using in vitro reconstitution assay are consistent with observations previously reported (15,16,19). We extended these investigations to include B-Raf kinase, an active mutant of C-Raf (C-Raf-Y340D/ Y341D) and the BXB form of C-Raf.…”
Section: Regulation Of B-and C-raf Kinasessupporting
confidence: 91%
See 3 more Smart Citations
“…5). Taken together, our results with respect to lipid binding performed with purified and functional full-length C-Raf kinases using in vitro reconstitution assay are consistent with observations previously reported (15,16,19). We extended these investigations to include B-Raf kinase, an active mutant of C-Raf (C-Raf-Y340D/ Y341D) and the BXB form of C-Raf.…”
Section: Regulation Of B-and C-raf Kinasessupporting
confidence: 91%
“…Specific Associations of B-and C-Raf Kinase with PS, PA, and Ceramides-Evidence that fragments of Raf proteins, particularly C-Raf-CRD, interact with phospholipids have been presented (15,16). The amino acids in C-Raf-CRD interacting with PS have been mapped as Arg-143, Lys-144, and Lys-148, since substitution of all three basic residues to alanine resulted in a C-Raf variant that failed to interact with PS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that the RafCRD is essential for Raf-1 activation (Clark et al, 1997;Luo et al, 1997;Roy et al, 1997). This domain has overlapping binding sites for phosphatidylserine (PS), Ras and 14-3-3 (Clark et al, 1997;Daub et al, 1998;Ghosh et al, 1996;Improta-Brears et al, 1999;Mott et al, 1996;Okada et al, 1999;Williams et al, 2000). It has been shown that the interaction of the CRD with 14-3-3 stabilizes the Raf-1/14-3-3 complex and that the incubation of Raf-1 with PS in vitro completely displaces 14-3-3 with a concomitant increase in Raf kinase activity (McPherson et al, 1999).…”
Section: Discussionmentioning
confidence: 99%